PENGARUH PENERAPAN SISTEM AKUNTANSI PEMERINTAH DAERAH, PENERAPAN ANGGARAN BERBASIS KINERJA, KEJELASAN SASARAN ANGGARAN, SISTEM PELAPORAN KINERJA DAN PENGENDALIAN AKUNTANSI TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (AKIP) (Study Kasus SKPD di Prov - Nurul Fathia; Yusralaini '; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aims to examine the influence of implementation local government accounting system, implementation performance based budgeting, Clarity of target budget, performance reporting system, and accounting system to the performance accountability for government agencies. Object of this research is local government unit who worked in Riau Province. There are 60 questionnaires were sent, and all of questionnaires are returned. The sample in this study are amounted to 60 respondents, 20 in government agencies and 3 sample in each agencies. The data ware using analyzed by linear regression method and SPSS program version 20. The variables were examined are influence of implementation local government accounting system, implementation performance based budgeting, Clarity of target budget, performance reporting system, and accounting system to the performance accountability for government agencies. Each independent variables, gives the strong influence to dependent variable, it means implementation local government accounting system, implementation performance based budgeting, Clarity of target budget, performance reporting system, and accounting system could explain the performance accountability for government agencies.Keywords : Government, Budgets, Performance, Accounting System.